The Islamic legal rulings on the composite transactions and its contemporary applications - Mohammad Hassan Hilal , Huda (2013)
This research aims to display the Islamic legal rulings on several types of composite transactions such as ‘Eenah, Tawarruq, Murabaha, and its contemporary applications such as; banking Tawarruq, reverse Murabaha, and the methods of practicing them in the current challenging world. ‘Eenah is considered forbidden in Maliki, Hanafi and Hanbali madhab because of its resemblance to Riba, but it is permissible in Shafi’i madhab because the process is valid. Tawarruq is permissible according to the majority, but Ibn Taymiyyah and Ibn Qayyim al-Jawziyah did not accept it because of the presence of usurious tricks. Murabaha initiated by the purchaser is practiced in conventional financing generated contracts in Islamic banks. The most applicable and common transactions in Modern financing generated contracts are banking Tawarruq and reverse Murabaha. Banking Tawarruq was permitted according to Islamic Fiqh council in1998, under a condition that the last selling is not less than the previous purchasing, but its legal ruling became forbidden after jurists suspected collusion between the bank and the client, and the falsity of the goods. The reverse Murabaha is where the customer finances the bank in buying an item, instead of the bank financing the customer. In order to use the composite transactions in the present, challenging times, there are some procedures that can be done; firstly, establishing an Islamic global market and secondly, cooperating between banks that are Islamic and conventional. Cooperation between Islamic banks requires offering tools for Islamic financing such as; Wadee’ah for short time, Murabaha credit line and reverse Murabaha. Cooperating with national conventional banks should be done according to the Shari’a; the central banks might provide them with governmental projects and the tools to realize this cooperation should be based on Murabaha and Mudarabah. Cooperation between international and Islamic banks can be done via different methods such as financing global trading stock based on reverse Murabaha, partnership in an overdraft account and credit line through Murabaha.